Effect of children's and parents' smoking on respiratory symptoms. Issue 2 (February 1978) - Bland, M; Bewley, B R; Pollard, V; Banks, M H
Abstract : It has been suggested that the apparent relationship between children's cigarette smoking and their respiratory symptoms could be explained by the effect of parents' smoking upon both child's smoking and symptoms. This was investigated in a study of 6000 Derbyshire schoolchildren. Children who smoked regularly were more likely than nonsmokers to report cough first thing in the morning, cough at other times during the day or at night, and breathlessness. Children whose parents smoked were also more likely to report these symptoms than were the children of nonsmokers. Both the child's and parents' smoking were independently related to the child's respiratory symptoms. Morning cough was less prevalent than cough at other times during the day or at night, but the relationship between the child's smoking and morning cough was much closer than its relationship to cough at other times. The relationship between parents' smoking and the child's symptoms was similar for each symptom.